Brucella Arthritis of Hip: A Case Report - Özlem Altındağ,; Fatma Sırmatel,; Öcal Sırmatel, (Archives of Rheumatology, 2007)
Brucellosis is a zoonosis that may affect almost any organ, notably the musculo-skeletal, cardiovascular and central nervous systems, sometimes with serious complications. Osteoarticular involvement is the most common complication of brucellosis. However, it can be difficult to diagnose it due to its nonspecific manifestations in musculoskeletal system. The painful limitation of movement may be the only articular sign in the involvement of the joint in Brucellosis. In this study we described a child with hip involvement of brucellosis who did not have any other systemic symptoms of brucellosis. It is suggested that brucellosis should be considered for those patients who have live in endemic regions. (Rheumatism 2007; 22: 40-2)